Respuesta :

Answer: The correct option is c.

Explanation:

Reason for correct option:

[tex]3x(9x^2+1)[/tex]

This expression cannot be factored further because [tex](9x^2+1)[/tex] is the complete factor. Therefore the option c is correct.

Reason for incorrect option:

[tex]5x^2-17x+14=5x^2-10x-7x+14=5x(x-2)-7(x-2)=(x-2)(5x-7)[/tex]

Since the given expression can be factored further therefore the option d is incorrect.

[tex]4(4x^4-1)=4((2x)^2-1)=4(2x^2-1)(2x^2+1)[/tex]

Since the given expression can be factored further. Therefore the option a is incorrect.

[tex]2x(y^3-4y^2+5y)=2xy(y^2-4y+5)[/tex]

Since the given expression can be factored further. Therefore the option b is incorrect.

The correct option is c).

Step-by-step explanation:

a) [tex]4(4x^4-1) = 4(2x^2-1)(2x^2+1)[/tex]

Therefore, option a) is incorrect because it can be further factorised.

b) [tex]2x(y^3-4y^2+5y)=2xy(y^2-4y+5)[/tex]

Therefore, option b) is incorrect because it can be further factorised.

c) [tex]3x(9x^2+1)[/tex]

This cannot be further factorised. Therefore, option c) is correct.

d) [tex]5x^2-17x+14=5x^2-10x-7x+14=5x(x-2)-7(x-2)= (x-2)(5x-7)[/tex]

Therefore, option d) is incorrect because it can be factorised completely.

For more information, refer the link given below

https://brainly.com/question/20293447?referrer=searchResults